Russian Academic Excellence—A Long Struggle - Altbach, Philip (International Higher Education, 2021)
The Russian excellence project, referred to as the 5–100 program, is coming to an end. While it did not accomplish one of its goals to catapult some Russian universities into the top 100 of the global university rankings, the project achieved a number of important objectives. These include internationalization, improved management, and strengthened research infrastructure and productivity. The Russian government is currently considering a new program for university improvement.